Brewer's spent grain as a no-cost substrate for polyhydroxyalkanoates production: Assessment of pretreatment strategies and different bacterial strains - Corchado-Lopo, Carlos; Martínez-Avila, Oscar; Marti, Elisabet; Llimós, Jordi; Busquets, Anna María; Kucera, Dan; Obruca, Stanislav; Llenas, Laia; Ponsá, Sergio (New biotechnology, 2021)
Polyhydroxyalkanoates (PHAs) are polyesters of significant interest due to their biodegradability and properties similar to petroleum-derived plastics, as well as the fact that they can be produced from renewable sources such as by-product streams. In this study, brewer's spent grain (BSG), the main by-product of the brewing industry, was subjected to a set of physicochemical pretreatments and their effect on the release of reducing sugars (RS) was evaluated. The RS obtained were used as a substrate for further PHA production in Burkholderia cepacia, Bacillus cereus, and Cupriavidus necator in liquid cultures. Although some pretreatments proved efficient in releasing RS (acid-thermal pretreatment up to 42.1 gRS L-1 and 0.77 gRS g-1 dried BSG), the generation of inhibitors in such scenarios likely affected PHA production compared with the process run without pretreatment (direct enzymatic hydrolysis of BSG). Thus, the maximum PHA accumulation from BSG hydrolysates was found in the reference case with 0.31 ± 0.02 g PHA per g cell dried weight, corresponding to 1.13 ± 0.06 g L-1 and a PHA yield of 23 ± 1 mg g-1 BSG. It was also found that C. necator presented the highest PHA accumulation of the tested strains followed closely by B. cepacia, reaching their maxima at 48 h. Although BSG has been used as a source for other bioproducts, these results show the potential of this by-product as a no-cost raw material for producing PHAs in a waste valorization and circular economy scheme.
Keywords: Pretreatments; Edible Grain; jedlá semena; Cupriavidus necator; Lignocellulosic material; Bacillus cereus; Waste valorization; Hydrolysate; polyhydroxyalkanoáty; Burkholderia cepacia; Polyhydroxyalkanoates